Locus of control, neuroticism and spirituality as predictors of waste-prevention behaviors - Karbalaei, Samaneh; Abdollahi, Abbas; Momtaz, Vahid; Abu Talib, Mansor (Mary Ann Liebert, Inc. Publishers, 2014)
Waste production is an important issue in both developed and developing countries; consequently, it is imperative to improve our knowledge about waste-prevention behaviors. This study aimed to investigate the relationships between locus of control, neuroticism, spirituality, and waste-prevention behaviors. Students (226 females and 214 males, from 17 to 46 years of age, M±SD=25.53±5.37) from Universiti Putra Malaysia were recruited for this study, and they completed self-report questionnaires. Structural equation modeling estimated that university students with internal personal control, higher levels of spirituality, and higher levels of neuroticism were more likely to report a positive attitude toward waste-prevention behaviors. These findings highlight the importance of personality traits in waste-prevention behaviors. Subsequently, the results demonstrated that waste-prevention behaviors can help prevent wasting economic efficiency and are vital to prevent nonrenewable resource depletion and environmental destruction. Key Words: Locus of control—Neuroticism—Spirituality—Waste-prevention behaviors.